ҚУЁШ СУВ ЧУЧУТГИЧ ҚУРИЛМАСИНИНГ САМАРАДОРЛИГИНИ ОШИРИШ УСУЛИ - Рахимов, Нурбек; Комилов, Аслиддин (Innovatsion texnologiyalar, 2022)
This article presents the relevance of desalination of salt water using solar energy, analysis of the design of existing solar desalination plants, methods for improving the efficiency of solar desalination plants and the principle of operation of a solar desalination plant with a turbo deflector.